Pemaknaan Khalayak Terhadap Androgini Pada Akun Instagram Andreas Lukita - Hizarani Lailan Saadah Sihombing; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is about the appearance of androgyny male beauty influencer from Indonesia named Andreas Lukita with Instagram account @alphamakeup. This research is interesting because the concept of beauty has been attached to women. Andreas Lukita is a male beauty influencer who looks androgynous through his instagram offers an alternative idea that not all men must look according to the standards of masculinity that apply in society and not all feminine criteria can only be owned by women. However, the meaning of active audiences is not necessarily in line with the alternative ideas that media texts are trying to offer on Andreas's Instagram. Thus, this study aims to describe the meaning of active audiences for androgyny in a photo uploaded by Andreas Lukita. Using a descriptive qualitative approach and the analysis method of the Stuart Hall reception, and the theory of Gender Performativity. The results of the study chose four preferred readings featuring Andreas Lukita's androgyny. The preferred reading shows the position of the informant who has a tendency to interpret negotiations. This is because the informants interpret the appearance of androgyny in a dilemma, where almost all informants approve and accept texts describing Andreas androgyny through the use of attributes that have strong associations with women such as makeup, fashion, and gestures. Informants interpreting androgyny is a form of performance carried out by Andreas Lukita because his profession as a beauty influencer, however, ignorance of androgyny, background, and cultural values makes stereotypes and representations that adversely participate in the process of interpreting informants. The informant said that they were still the same as the general public who polarized masculine and feminine gender based on sex. Thus, the androgyny presented by Andreas is seen as a form of male imitation of feminine gender, and is outside the normal conception prevailing in society. This shows that audiences can agree and negotiate men with androgyny appearance that is quite different from the dominant masculinity portrayal they were previously familiar with and that the public is active because they do not directly accept and interpret media messages, but are negotiated according to their background and conditions each audience.Meanwhile, without distinguishing sexes the phenomenon of beauty influencers is also inseparable from the presence of capitalism and industrial products.